THE MOTHER EARTH IN IGBO RELIGION - Onwurah, Emeka (Journal of Dharma, 1993)
African humanism is not individualistic, it is a communal humanism because the African finds his fulfilment not as a separate individual but as a participant in a family and a community. But although the human community is primary, the African is also related to the physical environment, especially to the land from which comes nourishment for life and in which the deceased members of the community are buried.